HRD Curriculum Meets Global Human Capital Challenge. (May 2017) - Gaudet, Cyndi H.; Brown, H. Quincy; Lunsford, Dale L.
The Problem: Human resource development (HRD) academic programs have grown and evolved over the last 25 plus years in a dynamic, global economy; yet, many HRD academic programs still grapple to define their role and purpose. Without the ability to clearly articulate the potential contributions undergraduate and graduate HRD programs offer the HRD profession, our universities, and global economy, we weaken our capacity to advance the field of HRD. Each year since 1999, The Conference Board, a global research association, has asked CEOs, presidents, and chair people across the globe to identify their most critical challenges. In the CEO Challenge 2015 and 2016 Reports, human capital was ranked as the number one global challenge. As the top challenge, CEOs view human capital in all its forms—from dynamic leadership to a skilled workforce cadre—as the primary fuel that will drive the engines of growth within their organizations. Undergraduate HRD programs are uniquely positioned to academically prepare entry-level professionals with the research-based knowledge, skills, and abilities required to develop the people needed for today's organizations; yet universities struggle to find appropriate patterns and themes for their curriculum. The Solution: This article provides a framework, an underlying structure, for undergraduate HRD academic programs mapped to strategies deployed globally by CEOs to meet their number one challenge of human capital—to build sustainable organizations and economies. Implications for developing undergraduate HRD curricula are included. The Stakeholders: HRD scholars, practitioners, and higher education administrators interested in the academic preparation of entry-level HRD professionals.